Effect of diluted and preheated oxidizer on the emission of methane flameless combustion - Hosseini, Seyed Ehsan (2012)
In combustion process, reduction of emissions often accompanies with output efficiency reduction. It means, by using current combustion technique it is difficult to obtainlow pollution and high level of efficiency in the same time. In new combustion system, low NOxengines and burners are studied particularly. Recently flameless or Moderate and Intensive Low oxygen Dilution (MILD) combustion has received special attention in terms of low harmful emissions and low energy consumption. Behavior of combustion with highly preheated air was analyzed to study the change of combustion regime and the reason for the compatibility of high performance and low NOx production. Sustainability of combustion under low oxygen concentration was examined when; the combustion air temperature was above the self-ignition temperature of the fuel. This paper purposes to analyze the NOx emission quantity in conventional combustion and flameless combustion by Chemical Equilibrium with Applications (CEA) software.